Phase-Based Tasks Scheduling in Data Centers Powered Exclusively by Renewable Energy - Caux, Stephane; Renaud-Goud, Paul; Rostirolla, Gustavo; Stolf, Patricia (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2019)
Data centers are considered nowadays as the factories of the digital age, being currently responsible for consuming more energy than the entire United Kingdom. On the other side, the global total capacity of renewable power increases continuously. The combination of these two factors calls for new approaches in designing data centers powered only by renewable energy sources. Our work focuses on task scheduling optimization under a power envelope, and on the way to handle power starvation, i.e. when the available power does not provide sufficient resources to execute a given workload. To do so we utilize the concept of task degradation through cross-correlation to find where to place the tasks in order to reduce the data center profit degradation. The results show that our algorithm could obtain more than 34% increase in profit when compared to algorithms from the literature, while fulfilling the power profile and resources constraints.